Water, Sanitation, and Hygiene Risk Factors on the Prevalence of Diarrhea among Under-Five Children in the Rural Community of Dangila District, Northwest Ethiopia - Bizuayehu Hailu; Wu Ji-Guo; Tadesse Hailu (Journal of Tropical Medicine)
Background. Under-five diarrhea is one of the major causes of morbidity and mortality in developing countries. Despite the tremendous achievement in reducing child mortality and morbidity in the last two decades, diarrhea is still the major causes of morbidity and mortality in resource-limited countries like Ethiopia due to the absence of clean water and poor sanitation and hygiene. Objective. This study aimed to assess the association of water, sanitation, and hygiene on the prevalence of diarrhea among under-five children in the rural community of Ethiopia. Methods. A cross-sectional study was conducted among randomly selected 419 under-five children from October to December 2021 in Dangila district, Northwest Ethiopia. A structured questionnaire was used to collect sociodemographic, environmental, and behavioral data. Data were entered into Epi Info and analyzed using SPSS software. Descriptive analysis was used to calculate the prevalence of diarrhea. Univariate and multivariate logistic regression were used to compute the association of water, sanitation, and hygiene with diarrhea. Statistical significance was considered if P<0.05. Results. Among 419 participants, the prevalence of diarrhea was 106 (25.3%). The absence of handwashing habit of children (AOR = 7.70; 95% CI: 2.71–21.79) and caregivers after toilet (AOR = 19.10; 95% CI: 5.46–66.52), absence of latrine (AOR = 3.87; 95% CI: 1.24–12.08), playing with soil (AOR = 8.40; 95% CI: 4.58–36.66), and eating soil (AOR = 6.24; 95% CI: 1.99–19.78) were significantly associated with under-five diarrhea. Children who drink unprotected water were 2.21 times (AOR = 2.21; 95% CI: 0.51–9.69) more exposed to under-five diarrhea than who drink protected water, but it is not statistically significant (P=0.29). Conclusion. The prevalence of under-five diarrhea is high in Dangila district. The absence of clean water and poor handwashing practice and the absence of latrine are the main factors associated with diarrhea. Therefore, strengthening water, sanitation, and hygiene strategy in the rural community should be prioritized.